Characterisation of the inflammatory response in Dupuytren's disease. Issue 3 (3rd May 2016) - Mayerl, Christina; Del Frari, Barbara; Parson, Walther; Boeck, Guenther; Piza-Katzer, Hildegunde; Wick, Georg; Wolfram, Dolores
Abstract: Background : Dupuytren's disease is characterised by fibrotic nodule and cord formation in the palmar aponeurosis. The pathophysiology of the disease is still unknown, although cell stress and subsequent activation of immune mechanisms seems to be crucial. Materials and methods : Surgically obtained tissue and blood samples of 100 Dupuytren patients were processed by immunohistochemistry, flow cytometry, as well as immunoscope analysis. Macroscopically normal aponeurotic tissue served as control. Results : Locally, microvascular alterations and massive infiltration by mononuclear cells (CD3+, CD4 > CD8, CD45RO > CD45RA, S100 protein, CD56, CD68, scarce CD19 and mast cells) forming perivascular clusters were found in DD tissue. Cytokine profiling of fibromatosis tissue-derived T-cells showed a Th1/TH17-weighted immune response. Immunoscope analysis revealed a restricted T-cell receptor α / β repertoire pointing to an (auto)antigen-driven process. Conclusion : The striking accumulation of immune cells, expression of leukocyte adhesion molecules, as well as pro-inflammatory and pro-fibrotic cytokines near markedly narrowed vessels supports the theory that the abnormal proliferation of fibroblasts and production of extracellular matrix proteins in DD seems to be related to immune-mediated microvascular damage. The restricted T-cell receptor repertoire of intra-lesional T-cells points to an antigen-driven process. T-cells seem to play an important role in the development of Dupuytren's disease.